MUSLIMAH BERCADAR (STUDI TENTANG PROSES INTERNALISASI DAN ADAPTASI SOSIAL MAHASISWI MUSLIMAH BERCADAR DI FAKULTAS EKONOMI UNIVERSITAS NEGERI MAKASSAR) - Marta Suharsih; Sopian Tamrin (PREDESTINATION: Journal of Society and Culture, 2020)
This study aims to determine: 1) the process of internalization of veiled Muslim female students, 2) social adaptation of veiled Muslim female students at the Faculty of Economics, Makassar State University. This type of research is descriptive qualitative research. The number of informants is 5 people. The selection of informants in this study by means of purposive sampling with the criteria of informants: a) students of the Faculty of Economics, Makassar State University class of 2015-2017, b) veiled Muslim female students, c) had used a veil for> 5 months. Data collection techniques used are observation, interviews and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions and verification. The data validation technique uses persistence of observation and triangulation. The results showed that: 1) the process of internalization of veiled Muslim female students at the Faculty of Economics, Makassar State University was carried out through several stages, namely the listening, responding, evaluating, organizing and characterization stages. 2) social adaptation of veiled Muslim female students is done by: a) Real appearance; manifested in the form of relationship skills and a willingness to be open to others, b) Adjustment to the group; manifested in the form of cooperation and social responsibility, c) social attitude; manifested in the form of participating in social activities, empathizing, and being able to respect and respect others.